Estudio de factibilidad para la implementación de un centro de capacitación ocupacional para adolescentes, parroquia 24 de Mayo, cantón Quevedo, Año 2014 - Zambrano Vargas, Ingrid Carolina (2015)
The objective of this research is a feasibility study for implementation of a Center for Occupational Training for Teenagers in the parish May 24, Quevedo Canton and is based on meeting the training needs of adolescents with high standards of quality, prices reasonable, and dedicated exclusively to the target according to the silver market objectives. Tools to improve the daily activities of young people, implementing appropriate programs eminently practical and participative methodology based on their own initiatives were implemented. In developing research, issues related to market research where the need in the parish May 24 this center of entrepreneurship for teenagers, a technical study which determined is identified are exposed to the full amount of the investments amounted to $ 41.313,00, also points the operating center will process and analyze the location, size, infrastructure, materials and equipment needed for implementation; in the economic study, positive earnings are determined during the lifetime of the project, resulting in the fifth year a total of $ 156.909,30 The statement says the fifth year a net profit of $ 32.967,54 then the financial….